2017
DOI: 10.1111/ejn.13745
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of microRNA and mRNA expression profiles in the rat spinal cord under inflammatory pain conditions

Abstract: Recent studies using microarray-based approaches have demonstrated that microRNAs (miRNAs) are involved in pain processing pathways. However, a significant proportion of computational predictions of miRNA targets are false-positive interactions. To increase the chance of identifying biologically relevant targets, we performed an integrated analysis of both miRNA and mRNA expression profiles in the rat spinal cord during complete Freund's adjuvant (CFA)-induced inflammatory pain. We generated miRNA and mRNA arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 81 publications
0
18
0
Order By: Relevance
“…Until now, many miRNAs, such as miR‐1247 and miR‐3941 have been reported to regulate LPS‐induced inflammatory damage in acute pneumonia . Previous evidence described that miR‐338‐3p was involved in the inflammatory damage in the rat spinal cord . Additionally, miR‐338‐3p was reported to weaken TNF‐α‐induced lipogenesis in sebocytes .…”
Section: Introductionmentioning
confidence: 99%
“…Until now, many miRNAs, such as miR‐1247 and miR‐3941 have been reported to regulate LPS‐induced inflammatory damage in acute pneumonia . Previous evidence described that miR‐338‐3p was involved in the inflammatory damage in the rat spinal cord . Additionally, miR‐338‐3p was reported to weaken TNF‐α‐induced lipogenesis in sebocytes .…”
Section: Introductionmentioning
confidence: 99%
“…Although only an array-based analysis focused on microRNA (miRNA) and mRNA network was used, they were still able to reveal that several miRNA-mRNA interactions contributed to the in ammatory pain process. For instance, they found that miR-124-3p could attenuate in ammatory pain and decrease IL-6R expression in the spinal cord [17]. Aside from this study, miRNAs have already been widely associated with in ammatory models [1; 12; 27; 33].…”
Section: Introductionmentioning
confidence: 52%
“…Interestingly, most of the differentially expressed miRNAs (104/120) were downregulated after CFA treatment. The global downregulation of miRNA itself is an interesting phenomenon, which was missed in the previous arraybased study [17]. Notably, in these downregulated miRNAs, many of them are targeting AP-1 network genes.…”
Section: Discussionmentioning
confidence: 86%
“…These studies suggested that epigenetic regulation, especially DNA methylation could contribute to in ammatory pain. In addition, although Tan et al provided rat SDH tissue expression pro les days after CFA treatment using microarray technology [17], the transcriptomic pro le of the dorsal root ganglion (DRG) tissues from the chronic pain animal models is still lacking. This suggested that how the gene expression is affected by CFA treatment in the primary sensory neurons is still not clear.…”
Section: Introductionmentioning
confidence: 99%